2020
DOI: 10.1111/nph.16480
|View full text |Cite
|
Sign up to set email alerts
|

δ15N values in plants are determined by both nitrate assimilation and circulation

Abstract: 2 UPR34 Performance des syst emes de culture des plantes p erennes, D epartement PERSYST, Centre de Coop eration Internationale en Recherche Agronomique pour le D eveloppement (CIRAD), SummaryNitrogen (N) assimilation is associated with 14 N/ 15 N fractionation such that plant tissues are generally 15 N-depleted compared to source nitrate. In addition to nitrate concentration, the d 15 N value in plants is also influenced by isotopic heterogeneity amongst organs and metabolites. However, our current understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…In the present study, the averaged whole plant Δ 15 N was 1.66‰, indicating that 14 NO 3 − was preferentially assimilated in the roots and a greater proportion of the 15 NO 3 − was returned to the hydroponic medium. Similar to the results of Kalcsits and Guy (2013a) for the closely related Populus balsamifera L. (balsam poplar), and many other species (Cui et al, 2020), we found leaves had higher δ 15 N values (i.e., lower Δ 15 N; Figure 4) than roots. This is the expected pattern if residual unassimilated NO 3 − (enriched in 15 N) is transported from roots to shoots.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, the averaged whole plant Δ 15 N was 1.66‰, indicating that 14 NO 3 − was preferentially assimilated in the roots and a greater proportion of the 15 NO 3 − was returned to the hydroponic medium. Similar to the results of Kalcsits and Guy (2013a) for the closely related Populus balsamifera L. (balsam poplar), and many other species (Cui et al, 2020), we found leaves had higher δ 15 N values (i.e., lower Δ 15 N; Figure 4) than roots. This is the expected pattern if residual unassimilated NO 3 − (enriched in 15 N) is transported from roots to shoots.…”
Section: Discussionsupporting
confidence: 89%
“…Although this is a high proportion relative to many species (Cui et al, 2020;Oh, Kato, & Xu, 2008), it is not unusual for Populus. Dluzniewska et al (2006) obtained a P root of 96% and Siebrecht and Tischner (1999) estimated P root to be 40 60%, both in hybrid aspen (Populus tremula × P. alba).…”
Section: N Concentration and 15 N-patterns Of Xylem Sapmentioning
confidence: 90%
See 2 more Smart Citations
“…In leaves, waterlogging leads to a strong increase in sugars (hexoses and polyols derived therefrom) and a decline in several amino acids (sometimes including alanine), suggesting an inhibition of sugar export and N assimilation [ 26 ]. In addition, there is a decline in nitrate content in leaves, much less pronounced in roots, suggesting an inhibition of xylem nitrate transport and in fact, computations based on 15 N natural abundance have shown a strong effect of waterlogging on nitrate circulation [ 28 ]. Additionally, in cotton, waterlogging causes a decline in the expression of nitrite reductase and an increase in nitrite concentration in leaves [ 29 ].…”
Section: Introductionmentioning
confidence: 99%